INTERNAL CONTROL SYSTEM IN LIGHT OF THE IMPACT OF THE DEMOGRAPHIC CHARACTERISTICS OF THE INTERNAL AUDITOR: AN APPLIED RESEARCH IN A SAMPLE OF GOVERNMENT UNITS IN NINEVEH GOVERNORATE (World Economics and Finance Bulletin, 2022)
The research aims to test the impact of the demographic characteristics of the internal auditor within government units in the internal control system. As the importance of the demographic characteristics of the internal auditor within six dimensions (job title, gender, years of service, academic achievement, courses, age) was dealt with in strengthening the foundations for protecting the assets of the Units Government departments according to the reality of the work of the internal control system, and the government departments subject to the review and audit of the Office of Financial Supervision in Nineveh Governorate were selected as a research field. The research found a positive significant correlation between the years of service characteristic of accountants and auditors with the level of evaluation of the internal control system of the study sample directorates. As whenever the accountants and internal auditors in the directorates have more years of service, this is accompanied by an improvement in the level of the internal control system by meeting more indicators specified by the Office of Financial Supervision for evaluating that system
Keywords: The demographic characteristics; the effectiveness of the internal control system; Nineveh Governorate